Mythological heroes on Czech stages and politics: the case of Phaethon and Antigone. (24th March 2023) - Čadková, Daniela
Abstract: Czech culture and society have abundant experience of repressive regimes and political oppression, as well as censorship and bans on speaking publicly and critically about the political situation. This article focuses on two dramatizations of ancient Greek myth and demonstrates their connection with politics: Phaethon by Otakar Theer (1917) is an expression of rebellion against the bondage of the Czech nation in the Austro-Hungarian Monarchy, while The Whore from the City of Thebes by Milan Uhde (1967), a paraphrase of Sophocles' Antigone, is a cynical analysis of the state of civil society in totalitarian communist Czechoslovakia. These plays tried to appeal to the audiences of the time allegorically, using 'Aesopian language' and parables. Both reinterpretations of Greek myth are analysed in their historical and cultural context and compared with contemporary adaptations of classical Greek tragedies.